Successes and challenges of insulin therapy for type 2 diabetes in a managed-care setting. - Nichols GA; Gandra SR; Chiou CF; Anthony MS; Alexander-Bridges M; Brown JB (Current Medical Research & Opinion, 2010)
OBJECTIVE: Although insulin is the most effective diabetes medication for lowering blood glucose, how insulin is used in clinical practice and how well patients respond to insulin therapy over the course of several years has not been documented. Our objective was to describe glycemic control, side-effects and dose titration over 7 years among persons starting insulin in a health plan that has long used a treatment algorithm similar to the current American Diabetes Association/European Association for the Study of Diabetes (ADA-EASD) algorithm for the management of hyperglycemia. RESEARCH DESIGN AND METHODS: Patients (n = 2417) who initiated insulin therapy between 1 January 1999 and 31 December 2004 were followed for a mean of 49.5 months until 30 June 2007, death, or health plan termination. Mean hemoglobin A1C, number of units of insulin purchased and body weight were assessed on a quarterly basis. The proportion experiencing edema or hypoglycemia was assessed annually. RESULTS: Mean population A1C declined from 9.3 to 7.8% following insulin initiation and remained at that level for 7 years. However, A1C remained above 8% for 40% of patients, half of whom remained above 9.0%. The mean individual coefficient of variation in A1C was 0.12 (inter-quartile range 0.072-0.143). Mean daily insulin dosage started at 55 units and increased to approximately 100 units. Patients gained a mean of 6 lb (2.7 kg) during the first year then gained weight more gradually thereafter. Physicians diagnosed edema in 8-9% of patients annually. Hypoglycemia occurred in fewer than 2% of patients in any given year, with no cases requiring hospitalization. CONCLUSIONS: Insulin lowered mean A1C by about 1.5 percentage points to stable levels, but this required ongoing dosage increases. Nevertheless, many patients remained in poor control. Insulin is effective when used per ADA-EASD guidelines but health plans wishing to optimize diabetes care may need to intensify insulin therapy or consider the use of adjunct therapies in the years after initiation. This study was limited by its observational descriptive design, and its reliance on insulin purchases rather than actual consumption.